FLORÍSTICA, FITOSSOCIOLOGIA E ETNOBOTÂNICA DA VEGETAÇÃO COSTEIRA DA RESERVA ESPECIAL DE MAPUTO, MOÇAMBIQUE - Ferreira, Elias Secretario Armando (2022)
The floristic, phytosociological, as well as the ethnobotanical formations of preserved forests is fundamental, especially for the conservation of biodiversity, which is one of the greatest challenges today due to the high level of disturbance of natural ecosystems, existing in Mozambique. The direction of the forest protects an important role in the protection of coastal dunes, which does not prevent the advance of sea waters in destruction of biodiversity along it. Furthermore, a preservation of this coastal ecosystem brings economic, environmental, social benefits and for the resident communities around it, as well as the tourist communities. In this context, there was a need to characterize the floristic, phytosociological and ethnobotanical aspects of the coastal coast of the Maputo Special Reserve, associating this knowledge and future conservation gains in local, regional and global terms. Therefore, this study according to the following methodological procedures: 1) The collection of samples of all the specimens was made, WHERE a collection of samples and samples of all their respective ones was made; 2) analysis of floristic similarity between the coastal forest of the Maputo Special Reserve and the namesakes of Mozambique, from other countries on the east and west coast of Africa; 3) the horizontal structuring of the sociological data, which consists of the data structure and the vegetation vertical; 4) characterization of the canopy opening; 5) pedological, WHERE the soil was collected; and 6) ethnobotanical survey, which had the help of semi-structured interviews and meetings with the local population. Data were analyzed by the PAST and RStudio program. Based on the data, we had the following results: a) the largest number of individuals are trees, of late secondary stage, without species at risk of extinction and of zoochoric seed dispersal and melitofolia pollination. The vegetation of the studied area is more similar to those of the east African coast and very little similar to those of the west coast of Africa. The different climatic environments that gave rise to different terrestrial ecoregions may have contributed to the high and low floristic similarity between the coastal flora of East Africa and West Africa. b) There are differences in structure and composition in the distribution of species in the forest remnant that was influenced by environmental variables such as calcium, potassium, sodium, humidity, canopy opening and organic matter. These results reinforced the need to create conservation strategies to minimize the degradation of coastal dunes in regions outside protected areas and the consequent loss of biodiversity in these forest ecosystems in these environments. c) All plant species were trees (100%). Mimusops caffra had the highest use value (2.56). The most cited categories were medicinal and construction (40 and 28%). The most cited medicinal plants were Acacia kraussiana and Bridelia cathartica. Most of the plant parts used are roots and stems (75%). The present study made a valuable contribution to the knowledge of the floristic composition, the structure of coastal vegetation, local knowledge and the benefits of the forest resources of the Maputo Special Reserve.